2022
DOI: 10.1021/acs.jmedchem.1c01682
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Inhibitors of the PD-1/PD-L1 Axis That Promote PD-L1 Internalization and Degradation

Abstract: Several monoclonal antibodies targeting the programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) pathway have been used successfully in anticancer immunotherapy. Inherent limitations of antibody-based therapies remain, however, and alternative small-molecule inhibitors that can block the PD-1/PD-L1 axis are urgent needed. Herein, we report the discovery of compound 17 as a bifunctional inhibitor of PD-1/PD-L1 interactions. 17 inhibits PD-1/PD-L1 interactions and promotes dimerization, internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 50 publications
2
61
0
Order By: Relevance
“…These 13 PDB structures were described in six peer‐reviewed journal publications by a number of research groups focused on discovering and developing orally bioavailable, small‐molecule drugs as alternatives to monoclonal antibody immune checkpoint anti‐cancer therapies. 107 , 108 , 109 , 110 , 111 , 112 , 113 Such ligands are thought to reduce tumor immune evasion via small molecule‐induced dimerization PD‐L1 and subsequent internalization. This effect on the immune checkpoint is mechanistically distinct from that of anti‐PD‐1 and anti‐PD‐L1 monoclonal antibodies, which interdict PD‐1/PD‐L1 mediated interactions between T‐cells and tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…These 13 PDB structures were described in six peer‐reviewed journal publications by a number of research groups focused on discovering and developing orally bioavailable, small‐molecule drugs as alternatives to monoclonal antibody immune checkpoint anti‐cancer therapies. 107 , 108 , 109 , 110 , 111 , 112 , 113 Such ligands are thought to reduce tumor immune evasion via small molecule‐induced dimerization PD‐L1 and subsequent internalization. This effect on the immune checkpoint is mechanistically distinct from that of anti‐PD‐1 and anti‐PD‐L1 monoclonal antibodies, which interdict PD‐1/PD‐L1 mediated interactions between T‐cells and tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was found that the binding of a biphenyl inhibitor to PD-L1 at the early stages of protein maturation suppresses protein glycosylation and prevents the transport of the under-glycosylated form of PD-L1 from the endoplasmic reticulum to the Golgi apparatus [131]. A recent report showed that the internalized PD-L1 is subjected to lysosome-dependent degradation triggered by biphenyl inhibitors (Figure 16) [132]. Based on the unique internalization and degradation mechanism of biphenyl-based small molecule inhibitors, derived radioligands could theoretically offer the possibility for an endoradiotherapy approach with beta-or alpha-emitting nuclides.…”
Section: Discussion and Outlookmentioning
confidence: 98%
“…Recently, Wang et al reported a discovery of a PD-1/PD-L1 small molecular inhibitor, which induced the dimerization of PD-L1, which was internalized into the cytosol, and degraded through a lysosome-dependent pathway 66 . From this point of view, inducing the formation of PD-L1 dimer would be a good strategy to reduce the concentration of PD-L1 and inhibit PD-1/PD-L1 pathway.…”
Section: Comparison Between the In Vitro Ic50 Of Camp On Pd-1/pd-l1 B...mentioning
confidence: 99%